Modeling the U.S. Climate Agenda : Macro-Climate Trade-offs and Considerations - Barrett, Philip; Bergant, Katharina; Chateau, Jean.; Mano, Rui. (Washington, D.C. : International Monetary Fund, 2021)
The run up to the 26th Climate Change Conference has brought tackling climate change to the fore of global policy making. In this context, the U.S. administration has recently unveiled new climate targets. This paper elaborates on the administration's plans and uses two models developed at the IMF to illustrate key macro-climate trade-offs. First, a model with endogenous fuel-specific technological change shows that subsidies cannot substitute for explicit carbon pricing and that even a moderate carbon tax can greatly economize on the overall fiscal cost of the package. Second, a rich sectoral model shows that there are only very marginal economic costs from front-loading the decarbonization of the power sector but there are large accompanying environmental benefits. Regulations can be effective in the power sector because they provide an appropriate shadow cost to carbon. However, a carbon tax would still be more efficient and easier to administer. Finally, as the economy transitions away from fossil-fueled power generation, there would be a significant reallocation of labor across sectors and locations that would need to be handled carefully to limit the social costs of the transition.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Carbon Tax; Climate Change; Renewable Resources and Conservation; Subsidies; Valuation of Environmental Effects